Evidence-Based Differentiated Instructional Methods: Foundation for an Intervention Programs in Social Studies - Tacorda, Arvin Nikko (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of differentiated instruction on secondary-level learners in Social Studies and the barriers experienced by teachers in its implementation. Guided by Multiple Intelligence Theory and organized through the Input-Process-Output framework, the study aimed to develop an intervention framework that could strengthen differentiated instruction practices. A qualitative exploratory research design was employed at Emilio Aguinaldo College. Seven regular secondary school teachers with experience in differentiated instruction were selected through purposive sampling. Data were gathered using a researcher-made questionnaire, a structured interview guide, and demographic profile sheets. The participants’ responses were transcribed, coded, and interpreted through thematic analysis. The findings revealed that differentiated instruction positively influenced learners’ academic performance, student engagement, classroom behavior, and skill progress. It supported personalized learning, improved comprehension, increased participation and confidence, promoted collaboration and autonomy, and strengthened communication, critical thinking, problem-solving, and social interaction. However, teachers encountered difficulties in assessing learners’ understanding, managing large classes, preparing differentiated lessons, designing rubrics and assessments, accessing adequate resources, managing limited instructional time, and adapting strategies to varied learner capabilities and interests. The study concluded that differentiated instruction could create a more inclusive, responsive, and learner-centered Social Studies classroom when supported by sufficient preparation, resources, and institutional assistance. It recommended professional development workshops, resource allocation, collaborative planning, mentorship, reflective practices, parent and community engagement, technology-supported learning, and regular curriculum review. The study supports SDG 4, Quality Education, by promoting inclusive and responsive teaching, and SDG 10, Reduced Inequalities, by addressing diverse learner needs. It also relates to SDG 17 through collaboration among teachers, administrators, families, communities, and policymakers. Its sustainability impact lies in strengthening long-term instructional quality, institutional support, inclusive education, and community participation.
Keywords: Academic Performance, Classroom Behavior, Differentiated Instruction, Inclusive Education, Intervention Framework, Secondary Learners, Skill Progress, Social Studies, Student Engagement